2021
DOI: 10.3390/fermentation7010008
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparative Study of the Malting Qualities of Winter Hull-Less and Hulled Barley (2016–2019)

Abstract: This paper aimed to compare the quality indicators of hull-less (naked) barley malt with malt obtained from hulled barley, according to the recommended values for standard pale malt. Five domestic hull-less barley varieties (Osvit, Mandatar, GZ-184, Osk.8.26/1–14 and Osk.6.24/4–12) and five hulled (Barun, OsLukas, Vanessa, Casanova, and Maestro) barley varieties were malted according to the standard procedure. The results of starting barley quality indicators (hectolitre weight, protein, starch, 1000 kernel we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…One of the major disadvantages of hull-less barley is that it displays a stronger resistance to grain modification. Recently, Habschied et al (2021) suggested that the intensification of malting process by hulless barley could be boosted by lowering temperatures during germination and with the extension of steeping time.…”
Section: Variation In β-Amylase Activity Of Different Barley Genotype...mentioning
confidence: 99%
“…One of the major disadvantages of hull-less barley is that it displays a stronger resistance to grain modification. Recently, Habschied et al (2021) suggested that the intensification of malting process by hulless barley could be boosted by lowering temperatures during germination and with the extension of steeping time.…”
Section: Variation In β-Amylase Activity Of Different Barley Genotype...mentioning
confidence: 99%
“…Each of the trends has certain requirements for the grain properties, which for the malting barley are opposed to feed and food purposes of use (Fang et al, 2019;Guo et al, 2020;Rani et al, 2021). The most suitable for malting are "traditional" covered awned barley varieties (Laidig et al, 2017;Gamayunova et al, 2021;Habschied et al, 2021;Ishchenko & Kozelets, 2021). Great advances in malting barley breeding have been achieved in Western Europe, as well as in some other countries of the World (Edney et al, 2014;Matthies et al, 2014;Mastanjević et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Barley (Hordeum vulgare L.) is one of the most important agricultural crops that satisfy the various needs of humanity (Mastanjević et al, 2017;Habschied et al, 2021). The genetic diversity of barley is greatly wide (Milner et al, 2019;Jayakodi et al, 2020;Hill et al, 2021).…”
Section: Introductionmentioning
confidence: 99%